Risks Elements of Electronic Records Management Systems in Institutions and Organizations: A Qualitative Review Based on Stakeholder Views - Eroğlu, Nagihan Gönül; Polat, Coşkun (Information World, 2025)
The transition from physical records management practices to electronic media has introduced various risks. Managing these risks, which, if left unchecked, can cause significant harm to organizations, including legal penalties, financial hardship, and loss of prestige, has become a crucial issue.This study was conducted to identify the risk factors encountered in Electronic Records Management Systems (ERMS) and their processes in institutions and organizations in Türkiye. It is anticipated that the research will help identify potential risk factors in ERMS and manage them more effectively. To this end, relevant literature studies, particularly standards and guidelines, were reviewed. Then, using a semi-structured interview technique, interviews were conducted with ERMS personnel responsible from 13 institutions and organizations, eight experts/academics in the field of records management, and three companies that developed ERMS software, and the risks encountered in practice were determined. Data obtained from the interviews were analyzed using MAXQDA software. The analyzes revealed that ERMS and processes face significant risks, including user errors, regulatory uncertainty/inadequacy, unpreparedness for unexpected events, technological change, organizational change, lack of institutional analysis, company dependency, security, and technical inadequacy. The findings demonstrate that the risks faced by institutions and organizations in our country related to ERMS and its processes are not solely software-related, but are multifaceted, with human, institutional, and national dimensions. The study offers recommendations for strengthening institutional awareness and interest in risk management to ensure the smooth operation of ERMS and processes.
Keywords: ERMS; electronic records management; electronic records management system; risk; risk management; risk in electronic records management